In search of a model of mentoring adult educators - Koutsoukos, Marios (Adult Education Critical Issues, 2022)
Since the Treaty of Lisbon in 2000, there has been a growing interest in the European area concerning mentoring in adult education, which, however, focuses on adult learners and is linked to their participation in educational programs as well as their inclusion in the labor market (Raschauer & Resch, 2016). This article focuses on adult educators and refers to research aimed at exploring adult educators’ views on mentoring as a tool to support their teaching work. The results showed that adult educators desire to mentor and describe a framework that incorporates the concepts of teamwork and reflection. On this basis, a group, reflective model of mentoring is proposed which aims to the inspiration, development, empowerment, and action of adult educators.